2018
DOI: 10.3389/fnbeh.2018.00299
|View full text |Cite
|
Sign up to set email alerts
|

A Longer Interstimulus Interval Yields Better Learning in Adults and Young Adolescents

Abstract: Eyeblink conditioning is one of the most popular experimental paradigms for studying the neural mechanisms underlying learning and memory. A key parameter in eyeblink conditioning is the interstimulus interval (ISI), the time between the onset of the conditional stimulus (CS) and the onset of the unconditional stimulus (US). Though previous studies have examined how the ISI affects learning there is no clear consensus concerning which ISI is most effective and different researchers use different ISIs. Importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Findings were most obvious in the first conditioning block. This agrees with the observation that learning occurs mainly in the first block of ten conditioning trials in humans (Kjell et al, 2018). Previous findings on accelerated eyeblink conditioning are based on experiments using the same CS in fear conditioning preceding eyeblink conditioning in rodents (Neufeld and Mintz, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings were most obvious in the first conditioning block. This agrees with the observation that learning occurs mainly in the first block of ten conditioning trials in humans (Kjell et al, 2018). Previous findings on accelerated eyeblink conditioning are based on experiments using the same CS in fear conditioning preceding eyeblink conditioning in rodents (Neufeld and Mintz, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Humans, however, acquire conditioned eyeblinks much faster than rodents (Spence, 1966). As stated above, the first conditioned eyeblink responses occur frequently within the first ten paired CS/US trials (Kjell et al, 2018). Much of the learning is achieved at the end of a single session, and additional increase of CR incidences across multiple sessions is comparatively small (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…The adults in our study show more CRs, greater prism adaptation, less tapping variability, and faster RT, than the children. Our previous studies showed that children older than 9 years old can reach the level of performance as young adults in acquiring CRs during eyeblink conditioning with a 500 ms ISI, whereas children younger than 9 years old acquire considerably less CRs 30,31 .…”
Section: Discussionmentioning
confidence: 95%
“…We also included 44 adults (26 females and 18 males), age 18-55 years (mean age = 27.9 years, SD = 8.2), recruited from the student population at Lund University. From the original sample size of 49 adult participants 31 , one was excluded due to very late reaction time responses (median = 364 ms) (method described below) and four due to technical issues during the eyeblink registrations. The adults displayed normal hearing (screening level 20 dB HL with pure tone audiometry by the modified Hughson-Westlake method, ISO 8253-1, with GSI 66 screening audiometer), 41 adults were right-handed and 3 left-handed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation